Optical and scintillation properties of stilbene polycrystalline and composite materials - Galunov, N.Z.; Tarasenko, O.A.; Tarasov, V.A. (Functional Materials, 2015)
The new types of organic radioluminescent materials, namely, polycrystalline and composite scintillators are studied. The results of measurements of light transmittance in the range of their luminescence and transparency are presented. The original data of light-collection coefficients, the absolute light yield, the total number of scintillation photons and the radioluminescence energy yield for organic heterogeneous scintillators irradiated by ionizing radiations of different types and energies are obtained. The comparison between the characteristics of the new types of radioluminescent materials and the structurally perfected single crystals are the base of the analysis. The scintillators on the base of stilbene are the object of investigation.